Auditory Screening of Basic School Children: A Comparison of Pure-Tone Audiometry and Impedance Audiometry - Azaglo, A. (University of Ghana, 2014)
School age children are faced with various forms of sensory disorders which impair academic, social and functional development. One of the most prevalent forms of sensory disorder is hearing loss. Auditory screening serves as an important process in identifying children with undetected hearing loss. The use of pure-tone audiometry has been the back bone of assessing children. In Ghana, auditory screening of school children has not been efficient due largely to the scarcity of resources including hearing health-care professionals’, audiometric equipment and over-reliance on pure-tone audiometry. Aim: The study investigated the impedance measurements against pure-tone audiometry as a screening method for the detection of middle ear changes associated with hearing loss in basic school pupils. Methodology: The study adopted a cross-sectional design which involved 2009 children within the age range of 4-15 years in four primary schools in Winneba community. The participants were examined with an otoscope, a tympanometer and an audiometer. Tympanograms were categorized into type A, B C AD and As while pure-tone audiometry utilized the conventional pass/refer criteria at 1, 2 and 4 kHz. Result: The results obtained showed that out of 3090 ears with type A tympanograms, 2.72% were referred in the pure-tone audiometry screening test. Also, 83.33% of 672 ears with type B tympanograms referred in the pure-tone screening 56.0% of 64 ears with type C tympanograms also referred in the pure-tone audiometry screening. None of the ears with type AD and AS were referred in the pure-tone audiometry screening test. Conclusion: The study concluded that auditory screening with tympanometry has a high rate of identifying children with hearing loss, as a result of middle ear pathologies and should be included in school screening exercises in Ghana. Keywords: tympanometry, auditory screening, impedance audiometry
Thesis (MSc) - University of Ghana,2014